Microsporidiosis in pediatric renal transplant patients in Cape Town, South Africa: Two case reports. (5th August 2014) - Ladapo, Taiwo A.; Nourse, Peter; Pillay, Komala; Frean, John; Birkhead, Monica; Poonsamy, Bhavani; Gajjar, Priya
Abstract Microsporidia are an emerging group of pathogens associated with life‐threatening opportunistic infections in immunocompromised hosts, particularly human immunodeficiency virus (HIV)‐infected individuals. There have, however, been recent reports of infection in adult solid organ transplant recipients. We report two cases in children, to our knowledge the first in the paediatric literature. Two 13‐yr‐old, HIV‐seronegative females received deceased donor renal transplants from the same donor. Both patients suffered acute cell‐mediated rejection and CMV infection reactivation, managed with intensified immunosuppression and ganciclovir. Pyrexia of unknown origin and intermittent diarrhea in both prompted extensive investigations. In both patients, numerous spores of a microsporidial species were demonstrated in renal tissue on biopsy and in the urine, using modified trichrome and quick‐hot Gram‐chromotrope staining. Electron microscopy and PCR confirmed Encephalitozoon cuniculi infections. Both patients were successfully treated with 400 mg twice daily of albendazole, with sustained clinical improvement. We recommend that microsporidiosis be considered in the differential diagnosis of pyrexia of unknown origin in severely immunocompromised pediatric solid organ transplant recipients, particularly when associated with diarrhea.